2002
DOI: 10.1038/sj.onc.1205784
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of multiple domains involved in the subcellular localization of the hematopoietic Pbx interacting protein (HPIP)

Abstract: We have previously reported the cloning of the Hematopoietic Pbx Interacting Protein (HPIP), a novel protein discovered through its interaction with Pbx1. HPIP is expressed in early hematopoietic precursors, can bind all members of the Pbx family and can inhibit the transcriptional activation of the oncogene E2A-Pbx. To further understand the function of HPIP, we have analysed its cellular localization and characterized its functional localization domains. Using fluorescence microscopy to follow the distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…The Pbx1/NMHCB interaction also supports the hypothesis that the actin cytoskeleton may play a role in the accurate regulation of the nuclear import of Pbx1. In agreement with this idea, the Haematopoietic Pbx1 Interacting Protein (HPIP), first identified as a PBX partner (Abramovich et al, 2000), has the potential to be a nucleocytoplasmic shuttle protein since it contains a NLS, a NES and a cytoskeletonbinding domain (Abramovich et al, 2002). Thus, the association of HPIP with the cytoskeleton may provide a regulatory mechanism controlling the availability of functional nuclear Pbx proteins.…”
Section: Resultsmentioning
confidence: 74%
“…The Pbx1/NMHCB interaction also supports the hypothesis that the actin cytoskeleton may play a role in the accurate regulation of the nuclear import of Pbx1. In agreement with this idea, the Haematopoietic Pbx1 Interacting Protein (HPIP), first identified as a PBX partner (Abramovich et al, 2000), has the potential to be a nucleocytoplasmic shuttle protein since it contains a NLS, a NES and a cytoskeletonbinding domain (Abramovich et al, 2002). Thus, the association of HPIP with the cytoskeleton may provide a regulatory mechanism controlling the availability of functional nuclear Pbx proteins.…”
Section: Resultsmentioning
confidence: 74%
“…Using the yeast two-hybrid system, we have identified an ER␣-interacting protein called hematopoietic PBX-interacting protein (HPIP; also known as PBX-interacting protein). HPIP is a transcriptional repressor of PBX1 (11) and has been shown to be associated with microtubules through a leucine-rich domain (12). Our data suggest that HPIP mediates binding of ER␣ with tubulins.…”
mentioning
confidence: 60%
“…Because HPIP contains both nuclear localization signals (NLS) and nuclear export signals (NES) (12) and ER␣ interacts with HPIP (this study), signals affecting microtubule-HPIP-ER␣ interaction may also influence HPIP and ER␣ nuclear localization and, hence, modify ER␣ transcriptional activity. In this context, it is notable that estrogen has been shown to inhibit the assembly of microtubules (15).…”
Section: Discussionmentioning
confidence: 99%
“…That study suggested investigating the possible relation of HPIP with signaling pathways (Manavathi et al, 2006). At that point, the only pertinent literature described HPIP as a novel protein detected only in proliferative cells (Manavathi et al, 2006;Abramovich et al, 2000Abramovich et al, , 2002. Our hypothesis was to show the presence of HPIP in neurons and a possible relationship among HPIP-microtubule-estrogen receptors and signaling pathways.…”
Section: Fold Change In Hpipmentioning
confidence: 90%
“…It has been shown that HPIP may be a tether between ER and microtubules. Some studies showed that short-term estrogen treatment increased ER interaction with the HPIP-microtubule complex (Manavathi et al, 2006;Abramovich et al, 2000Abramovich et al, , 2002.…”
Section: Introductionmentioning
confidence: 98%